DFT Study of Photoelectric Properties of Some Organic Polymers - KUEVI, URBAIN AMAH (My University, 2017)
Polyacetylens noted PA, with general formulae () nCHCH−=− are organic compounds with double conjugated bonds. They are the thirst polymers conducting characters which, after doping, were highlighted. Indeed, the semiconducting character of an organic material resides in the alternation of single and double covalent bonds; the π bonds electrons, in these conditions, are able to be delocalization. That delocalisation assures the transport of charges. The substitution derivatives of these compounds may exhibit better conduction capabilities. Since AP and their derivatives, like many other organic conjugated materials, absorb electromagnetic waves in the visible range of the spectrum, they are used as photovoltaic materials, essential parts of organic solar cells. The present work focused on the theoretical study of the evolution of the photovoltaic character of PA and their halogenated derivatives as a function of their polymerization index (n, n = 1 to 5); this study was carried out consideration the energy gaps between the LUMO and the HOMO of the molecules involved in this work and confirmed the experimental results known in the literature. The calculations were performed by the DFT / B3LYP method in the 6-31g+(d,p) orbital basis. The Gaussian program in its versions 98, 03 and 09 was used to perform these calculations on the HPL1908w, Samsung Intel® Core i3-3110 CPU and Dell computers. After comparing the differences between the LUMO of the molecules, it has been proposed to use photovoltaic “donor-acceptor” combinations based on anthracene and polyacetylene.
Keywords: Polyacetylens; Anthracene; Photovoltaic conjugated organic materials; LUMO; HOMO; DFT/B3LYP; Base 6-31g+(d; p)